Carbon fibres with modulated properties and shape along the fibre length - Blaker,JJ; Anthony,DB; Tang,G; Shamsuddin,S; Abdolvand,A; Shaffer,M; Bismarck,A (ICCM, 2015)
This paper presents a detailed experimental examination of the influence of the thickness of flatenergy directors (ED) on the ultrasonic welding (USW) process for carbon fibre/polyetherimidecomposites. Three thicknesses of flat ED were compared: 0.06 mm, 0.25 mm and 0.50 mm. Power anddisplacement data for 0.06 mm-thick EDs did not clearly show the stages of the process and thelocation of the optimum for best weld quality. Consequently, an investigation of samples welded atdifferent stages in the welding process had to be performed. For 0.06 mm-thick EDs, the optimum wasdetermined to occur at the beginning of the downward displacement of the sonotrode in the vibrationphase. The output parameters at the optimum conditions for all thicknesses were compared. Averagelap shear strength was found to be lowest for 0.06 mm-thick EDs. Based on the analysis of the fracturesurfaces, resin flakes and voids were observed when using the thinnest energy directors, indicatingthermal degradation. These observations suggest that thin energy directors are not as efficient asthicker EDs (i.e. 0.25 mm) to achieve preferential heat generation at the weld line, leading to lessconsistent weld quality.